2010
DOI: 10.1007/s10532-010-9377-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel aerobic benzene degrading microorganisms identified in three soils by stable isotope probing

Abstract: The remediation of benzene contaminated groundwater often involves biodegradation and although the mechanisms of aerobic benzene biodegradation in laboratory cultures have been well studied, less is known about the microorganisms responsible for benzene degradation in mixed culture samples or at contaminated sites. To address this knowledge gap, DNA based stable isotope probing (SIP) was utilized to identify active benzene degraders in microcosms constructed with soil from three sources (a contaminated site an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 94 publications
3
33
0
Order By: Relevance
“…Aerobic degradation of these chemicals is generally rapid (39,56,62); however, in the saturated subsurface, anaerobic conditions typically exist. Therefore, understanding anaerobic biodegradation is also relevant to site cleanup.…”
mentioning
confidence: 99%
“…Aerobic degradation of these chemicals is generally rapid (39,56,62); however, in the saturated subsurface, anaerobic conditions typically exist. Therefore, understanding anaerobic biodegradation is also relevant to site cleanup.…”
mentioning
confidence: 99%
“…Acidobacteriarelated bacteria have been proved in the degradation of petroleum [50], PAHs [33,50], and PCBs [32,50] in various habitats. To date, SIP has been successfully applied to investigate the ability of Acidobacterium to metabolize propionate [51], biocide [52], herbicide [53], and benzene [29]. Our recent SIP research also demonstrated that Acidobacteria-related bacteria were related to the degradation of PHE in forest soil [26].…”
Section: Discussionmentioning
confidence: 94%
“…Clones with the predicted cut sites matching TRFLP cut sites of the corresponding TRFs were selected for phylogenetic analysis. Previous studies have shown that small differences (2-3 bases) often occur between the measured fragment lengths and those predicted using sequence data [29,30]. Clones with predicted cut sites matching 291-bp TRF (based on the analysis of the clone sequences, each with a predicted HaeIII cut site of 294 bp) accounted for the majority of microbes in the clone library.…”
Section: Microbial Structure Analysis Via Sip and Trflpmentioning
confidence: 93%
“…Previously, SIP investigations of the metabolism of benzene, toluene, ethylbenzene, and xylene (BTEX) compounds largely focused on anaerobic benzene and toluene degradation, using PLFA and rRNA-based fingerprinting techniques to identify the active populations (32)(33)(34)(35). DNA-and RNA-based benzene SIP investigations have been conducted in coal tarcontaminated sediment, gasoline-contaminated water, and soil (31,36,37). However, the high diversities of habitat types and geochemical conditions where contaminants occur warrant additional SIP investigations.…”
mentioning
confidence: 99%